A randomized, double‐blind, placebo‐controlled study of the kappa opioid receptor antagonist, CERC‐501, in a human laboratory model of smoking behavior. (26th June 2019) - Jones, Jermaine D.; Babalonis, Shanna; Marcus, Ronald; Vince, Bradley; Kelsh, Debra; Lofwall, Michelle R.; Fraser, Heather; Paterson, Blake; Martinez, Suky; Martinez, Diana M.; Nunes, Edward V.; Walsh, Sharon L.; et al.
Abstract: Preclinical data indicate that selective kappa opioid receptor antagonists reduce nicotine self‐administration and withdrawal symptoms. The aim of the current study was to determine whether treatment with CERC‐501, an orally available, potent, and selective kappa opioid receptor antagonist, could alleviate nicotine withdrawal and craving and mitigate mood alterations associated with nicotine withdrawal in humans. Healthy, adult cigarette smokers were enrolled into this randomized, multisite, double‐blind, placebo‐controlled, crossover study. Participants completed two 8‐day treatment phases during which they received either CERC‐501 (15 mg, p.o., once daily) or placebo. On the seventh day of each dosing phase, participants were admitted as inpatients for an 18‐hour cigarette abstinence period followed by experimental testing. The primary outcome measures were (a) performance on the McKee Smoking Lapse test (ie, latency to smoke in exchange for money) and (b) number of cigarettes self‐administered during a 60‐minute ad lib smoking period. Other outcomes included measures of craving, mood, anxiety, nicotine withdrawal, and subjective effects of cigarette smoking. A total of 71 participants who smoked an average of approximately 23 cigarettes per day were enrolled, and 56 subjects completed the study. CERC‐501 was well tolerated, but it did not significantly alter the latency to start smoking (CERC‐501: 16.5 min vs placebo: 17.7 min) or the number of cigarettes smoked (CERC‐501: 3.3 cigarettes vs placebo: 3.1 cigarettes). Compared with placebo, CERC‐501 also did not affect cigarette craving, mood, anxiety, nicotine withdrawal, or subjective effects of smoking. These findings do not support a role for CERC‐501 in the treatment of nicotine use disorder. Abstract : CERC‐501 is an orally bioavailable, high‐affinity, selective kappa opioid receptor antagonist. CERC‐501 maintenance failed to alter smoking behavior or nicotine withdrawal after 18‐hour cigarette abstinence. These findings do not support a role for CERC‐501 in the treatment of nicotine use disorder. These findings do not support a role for CERC‐501 in the treatment of nicotine use disorder.